Salicylic acid immersion maintains physiochemical quality and enhances bioactive compounds in 'Kimju' guava fruit during cold storage - Supapvanich, Suriyan; Mahasap, Boonwat; Boonyaritthongchai, Panida; Techavuthiporn, Chairat; Tepsorn, Racha; Youryon, Pannipa (My University, 2017)
The aims of this work were to investigate the effect of salicylic acid (SA) immersion on the physicochemical quality maintenance and biologically active compounds enhancement of 'Kimju' guava. The fruit were immersed in water (control) and 2 mM SA solution and stored at 12 ± 1 °C, 90 ± 2% RH. The observed factors were pigments, total sugars, total soluble solids (TSS), total acidity (TA), firmness and pectin components, bioactive compounds such as ascorbic acid (AsA), total phenols (TP), total flavonoids (TF) and the activities of antioxidant enzymes including peroxidase (POD) and catalase (CAT). The total chlorophylls chlorophyll a and b contents of the treated fruit were higher than those of the control. The SA immersion did not affect the total carotenoids concentration and TSS whilst it delayed the increase in total sugars and lowered TA content. The fruit softening was delayed by the SA immersion due to the control of soluble pectin increase and insoluble pectin decrease. The antioxidant activity and the concentrations of AsA, TP and TF were enhanced by the SA immersion. The SA immersion also stimulated POD activity but did not induced CAT activity. In conclusion, 2.0 mM SA immersion is an effective postharvest treatment maintaining quality and improving nutritional values of 'Kimju' guava.
Keywords: Bioactive compounds; Firmness; Guava; Nutritional quality; Salicylic acid